EDUCATIONAL ASPECTS IN SOCIAL WORK: EXPERIENCE&NBSP;OF COMMUNAL EMPOWERMENT - Dirgėlienė, Indrė (Acta Paedagogica Vilnensia, 2010)
The multidisciplinary nature of social work discribed in the article focuses on education expression in the process of client empowerment. A holistic approach is applied in the empowerment process: experience of communal empowerment is actualized in the context of training life success. Expression of educational aspects as well as the perspective in the process of the client empowerment are foreseen seeking purposes of re-socialisation. This research project was aimed at focusing upon the formative aspects of social work, so as to reveal educational aspects of social work based on the experience of communal empowerment. The interviews selected for content analysis were structured according to I. Marshall (2006) and his motivational scale. Interviews were conducted in Klaipeda between 2008 and 2010 with six clients (five male, one female) who had previously served prison sentences. The research revealed the complexity and the sources of psycho-social problems of former prisoners. Comparative analysis of the life before joining the rehabilitative community and the results of communal empowerment reveal the relevance of educational activity and methods in the process of the client‘s empowerment. The analysis of educational aspects of social work would give the possibility to enrich educational theory and practice.